Vision difficulty and dementia: economic hardships among older adults and their caregivers - Kumar, Priyanka; Chung, Grace; Garcia-Morales, Emmanuel; Reed, Nicholas S.; Sheehan, Orla C.; Ehrlich, Joshua R.; Swenor, Bonnielin K.; Varadaraj, Varshini (Frontiers in Epidemiology, 2023)
Introduction Limited research has examined the economic impact of vision difficulty (VD) and dementia on older adults and their caregivers. We aimed to determine whether older adults with VD and/or dementia, and their caregivers, face more economic hardships than their counterparts without VD or dementia. Methods We used cross-sectional data from the 2015 National Health and Aging Trends Study (NHATS), a population-based survey of Medicare beneficiaries, linked to their family/unpaid caregivers from the National Study of Caregiving (NSOC). Regression models characterized the association of VD (self-report), dementia (survey and cognitive assessments), and co-occurring VD and dementia with debt, receiving financial help from relatives, government-based Supplemental Nutrition Assistance Program (SNAP), other food assistance, utility assistance, and caregiver financial difficulty. Results The NHATS sample included 6,879 community-dwelling older adults (5670 no VD/dementia, 494 VD-alone, 512 dementia-alone, 203 co-occurring VD and dementia). Adults with VD and dementia had higher odds of receiving SNAP benefits (OR = 2.6, 95%CI = 1.4–4.8) and other food assistance (OR = 4.1, 95%CI = 1.8–9.1) than adults without VD/dementia, while no differences were noted for debt, financial help, and utility assistance. Adults with VD-alone had higher odds of debt (OR = 2.1, 95%CI = 1.3–3.2), receiving financial help (OR = 1.7, 95%CI = 1.1–2.5) and other food assistance (OR = 2.7, 95%CI = 1.7–4.3); while adults with dementia-alone had higher odds of debt (OR = 2.8, 95%CI = 1.4–5.5). The NSOC sample included 1,759 caregivers (995 caring for adults without VD/dementia, 223 for VD-alone, 368 for dementia-alone, and 173 for co-occurring VD and dementia). Compared to caregivers of older adults without VD/dementia, caregivers of adults with VD and dementia had higher odds of financial difficulty (OR = 3.0, 95%CI = 1.7–5.3) while caregivers of adults with VD-alone or dementia-alone did not. Discussion While older adults with VD- or dementia-alone experienced increased economic hardships, disparities in food assistance were amplified among older adults with co-occurring disease. Caregivers of adults with co-occurring disease experienced more financial difficulty than caregivers of adults with a single or no disease. This study highlights the need for interventions across clinical and social services to support the economic wellbeing of our aging population and their caregivers.